2016
DOI: 10.1038/srep25689
|View full text |Cite
|
Sign up to set email alerts
|

Activated Stat5 trafficking Via Endothelial Cell-derived Extracellular Vesicles Controls IL-3 Pro-angiogenic Paracrine Action

Abstract: Soluble factors and cell-derived extracellular vesicles (EVs) control vascular cell fate during inflammation. The present study investigates the impact of Interleukin 3 (IL-3) on EV release by endothelial cells (ECs), the mechanisms involved in EV release and paracrine actions. We found that IL-3 increases EV release, which is prevented by IL-3Ralpha blockade. EVs released upon IL-3 stimulation were able to induce pro-angiogenic signals as shown by chromatin immunoprecipitation (ChIP) assay performed on the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
75
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(78 citation statements)
references
References 60 publications
(95 reference statements)
2
75
1
Order By: Relevance
“…5×10 5 cells/well of MCs were incubated with a transcriptional inhibitor, α-amanitin [31], either in the absence or in the presence of EVs that had either been pre-treated with RNAse or not. Total RNA from MCs, was subjected to qRT-PCR for miR expression.…”
Section: Methodsmentioning
confidence: 99%
“…5×10 5 cells/well of MCs were incubated with a transcriptional inhibitor, α-amanitin [31], either in the absence or in the presence of EVs that had either been pre-treated with RNAse or not. Total RNA from MCs, was subjected to qRT-PCR for miR expression.…”
Section: Methodsmentioning
confidence: 99%
“…Selective supportive conditions of the bone marrow (BM) microenvironment, especially BM angiogenesis (26), are involved in the development of MM. Microvesicles (MVs), also called microparticles, range in size from 100 to 1000 nm in diameter, are formed by the outward blebbing of the plasma membrane and are known as important players in the cell-to-cell communication that occurs in normal physiology and in pathological conditions such as the angiogenic process (10)(11)(12)(13)(14). A recent study has shown that MM-derived MVs (MM MVs) are internalized by endothelial cells and promote angiogenesis (14) in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Microvesicles (MVs), a type of extracellular vesicles (EVs), are also called shedding vesicles or microparticles (MPs) and have emerged as important players in cell-to-cell communication (6)(7)(8). MVs can load and transmit bioactive molecules to target cells (9)(10)(11) and induce different signaling cascades (10,12,13). A previous study found that MVs derived from MM cells (MM MVs) can be internalized by endothelial cells and promote angiogenesis (14).…”
Section: Introductionmentioning
confidence: 99%
“…Some non‐TDEs with potential pro‐angiogenic functions are also involved in angiogenesis within pre‐metastatic niche. These non‐TDEs are usually secreted by several tumor‐associated stromal cells, like tumor‐associated macrophages, platelets, endothelial cells, etc …”
Section: Exosomes In Sequential Processes Of Tumor Metastasismentioning
confidence: 99%
“…These non-TDEs are usually secreted by several tumor-associated stromal cells, like tumor-associated macrophages, platelets, endothelial cells, etc. 80 Lymphangiogenesis is actively involved in the premetastatic niche. Lymphatic vessels may serve as initial routes for tumor lymphatic dissemination.…”
Section: Exosomal Integrin Model Only Until 2015 Hoshino Et Almentioning
confidence: 99%